2011
DOI: 10.1002/ijc.26022
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease and stroke before and during endocrine treatment for prostate cancer in PCBaSe Sweden

Abstract: In observational studies of men with prostate cancer, men on endocrine treatment (ET) have had an increased risk of ischemic heart disease (IHD) and stroke. However, prostate cancer per se may increase risk of IHD and stroke and men on ET may have been at increased risk already prior to initiation of ET. We assessed the incidence of IHD and stroke in men with prostate cancer before and during different endocrine treatments. The hazard ratio (HR) of IHD and stroke in 39,051 men with prostate cancer vs. a matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Our findings also are consistent with autopsy study of Stamatiou suggesting that men with PCa had greater advanced atheromatosis than subjects without PCa [30]. A study of 30,883 men with PCa hormone-naive, showed a statistical significantly increase in risk of ischemic heart disease for all men with PCa versus controls [33]. Similarly, Zoller et al showed an increased risk of CAD during the first 6 months after diagnosis of PCa and after 10 years after diagnosis of cancer [34].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also are consistent with autopsy study of Stamatiou suggesting that men with PCa had greater advanced atheromatosis than subjects without PCa [30]. A study of 30,883 men with PCa hormone-naive, showed a statistical significantly increase in risk of ischemic heart disease for all men with PCa versus controls [33]. Similarly, Zoller et al showed an increased risk of CAD during the first 6 months after diagnosis of PCa and after 10 years after diagnosis of cancer [34].…”
Section: Discussionsupporting
confidence: 91%
“…A recent Swedish population-based study demonstrated that, regardless of treatment, men with prostate cancer exhibited a small increase in stroke risk, compared with an age-matched control population. However, the initiation of endocrine treatment is not associated with an increased risk of stroke (25). A 5-year follow-up study in Taiwan presented a similar conclusion, showing no significant difference in stroke risk between ethnic Chinese patients with prostate cancer who did vs those who did not receive ADT (26).…”
Section: Discussionsupporting
confidence: 60%
“…One [24] of these four studies [4], [13], [24], [25] using the same database were included because of more complete and recent data. Meanwhile, among another three studies [26][28] coming from the same database, Hemelrijck et al's [28] was included at last for the complete data. Two [29], [30] were excluded because the database were not population-based.…”
Section: Resultsmentioning
confidence: 99%